The Effect of Using Digital Bamboozle Game Toward Students’ Vocabulary Mastery on Eight Grade Students’ at SMP Negeri 14 Seluma - Fitriani Fitriani; Ferri Susanto; Dedi Efrizal (Lembaga Pengembangan Kinerja Dosen, 2025)
The researcher found several problems faced by teachers and students in the English learning process in the classroom, one of which is students' limited vocabulary mastery. One of the efforts made to help students in mastering vocabulary is through fun methods, namely using games. This study aims to determine whether there is a significant effect of using the digital game Bamboozle on vocabulary mastery in class eight students of SMP Negeri 14 Seluma Regency. This research used quantitative method with quasi-experimental design. The population in this study were all eight grade students of SMP Negeri 14 Seluma. The sampling technique used was purposive sampling, with class eight E as the experimental class and class eight D as the control class. Data were collected through a multiple choice vocabulary test of 27 questions. The data obtained was analyzed usingT-test and F-test formulas. Researcher found that there was an increase in the post-test. The average value of the experimental class was 66.13 in the pretest and 86.53 in the posttest. The T-test result is higher than the t-table (7.419 > 1672) and the F-test is higher than the f table (55.039 > 4.00). Thus it can be concluded that there is a significant effect of using digital bamboozle game toward students’ vocabulary mastery on eight grade students’ at smp negeri 14 seluma.